Interactions between polystyrene nanoparticles and Chlamydomonas reinhardtii monitored by infrared spectroscopy combined with molecular biology. (November 2020) - Déniel, Maureen; Errien, Nicolas; Lagarde, Fabienne; Zanella, Marie; Caruso, Aurore
Abstract: For several decades, use of nanoparticles (NP) on a global scale has been generating new potential sources of organism disruption. Recent studies have shown that NP can cause modifications on the biochemical macromolecular composition of microalgae and raised questions on the toxicity of plastic particles, which are widespread in the aquatic environment. Polystyrene (PS) particles are among the most widely used plastics in the world. In our experimentation, a combined approach of infrared spectroscopy and molecular biology (real-time PCR) has been applied in order to better apprehend the consequences of interactions between Chlamydomonas reinhardtii, freshwater microalgae and PS NP. Two references have been used, nitrogen deprivation -a well-documented stressor-, and gold nanoparticles (Au-NP). As regards biochemical composition, our experiments show a differing microalga response, according to the NP to which they have been exposed. Results with infrared spectroscopy and gene expression methods are consistent and illustrate variation among several carbohydrates (galactose…). Furthermore, PS-NP seem to react in the same direction as nitrogen limitation, thereby supporting the hypothesis that PS-NP can induce response mechanisms to environmental changes in microalgae. This study highlighted the interest of combining infrared spectroscopy and gene expression as means of monitoring microalgae response to nanoplastics. Graphical abstract: Image 1 Highlights: Proteins and carbohydrates bands modifications have showed in presence of PS NP. Spectral deconvolution permits to outline carbohydrates band variations. Gene expression results outlines a variation of carbohydrates biosynthesis pathways. Combined techniques supporting that PS NP could induce microalgae answer mechanisms. Abstract : Nanoplastics interactions induce polysaccharides variations content of C. reinhardtii highlighted by infrared spectroscopy and molecular biology.